Impact of Covid-19 on Profitability on Company Value Mediated By Dividend Policy as Intervening Variable - Herry Subagyo (Budapest International Research and Critics University, 2022)
This study aims to see and compare the connection between profitability, managerial ownership and company size to the value of real estate and property firms in the pre-pandemic period and the ongoing pandemic period. The property and real estate companies studied were only those registered on the Indonesia Stock Exchange (IDX) for 7 years from 2019 to 2020. The sample consisted of 97 companies based on the sample criteria determined by the purposive sampling method. Obtain financial data from the Indonesian Capital Market Directory published by the IDX. The data processing approach uses SEM-PLS with WarpPLS 7.0 as an analysis tool. The results of the study explain that the influence of the pandemic makes companies have to continue to carry out their activities, in this study dividend policy is an intervening or mediating variable, but it cannot be proven by data processing carried out. This can be explained by the bird in hand theory that profits should be distributed not held for shareholders, during the current pandemic it is very risky to invest.